1993
DOI: 10.1161/01.hyp.21.3.373
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of hypertriglyceridemia in Dahl rats.

Abstract: Plasma triglyceride concentrations were shown to be higher in hypertensive (153±2 mm Hg) male Dahl salt-sensitive rats than in control Sprague-Dawley rats (122 ±2 mm Hg). These differences in triglyceride concentrations were seen when blood was drawn at 9 AM from unfasted animals (229±27 versus 111±8 mg/dL), at 1 PM after a 4-hour fast (186±13 versus 88±4 mg/dL), or at 9 AM after a 13-hour fast (151±6 versus 90±6 mg/dL), all p<0.001. Total triglyceride secretion was also compared in groups of rats by determini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…The authors suggest the activation of lipoprotein lipase in white adipose tissue as a potential cause of the apparent disconnect between plasma triglycerides and increased triglyceride secretion. Conclusions put forth by Sato et al [47] are consistent with increased hepatic triglyceride secretion and decreased removal of plasma triglycerides observed in Dahl salt-sensitive rats [48] and increased production and reduced clearance of very low density lipoprotein particles in humans (see [28]. The scope of our study is not sufficient to elucidate the disconnect between fat pad weight and plasma levels of triglycerides, but the genes associated with metabolism, lipogenesis and accumulation of lipoproteins may be located on SSBN8.…”
Section: Discussionsupporting
confidence: 69%
“…The authors suggest the activation of lipoprotein lipase in white adipose tissue as a potential cause of the apparent disconnect between plasma triglycerides and increased triglyceride secretion. Conclusions put forth by Sato et al [47] are consistent with increased hepatic triglyceride secretion and decreased removal of plasma triglycerides observed in Dahl salt-sensitive rats [48] and increased production and reduced clearance of very low density lipoprotein particles in humans (see [28]. The scope of our study is not sufficient to elucidate the disconnect between fat pad weight and plasma levels of triglycerides, but the genes associated with metabolism, lipogenesis and accumulation of lipoproteins may be located on SSBN8.…”
Section: Discussionsupporting
confidence: 69%
“…During hypertension, LPL activity is reduced in skeletal muscle and adipose tissue in human patients 32,33 and in Dahl saltsensitive rats. 34 We recently reported that the heparin-releasable LPL fraction in SHR hearts is reduced relative to that of WKY rats. 22 Because nifedipine and CGS-21680, vasodilators with divergent mechanisms of action, normalized enzyme release, we concluded that flow through coronary blood vessels might influence LPL activity.…”
Section: Discussionmentioning
confidence: 96%
“…They show rapid onset of hypertension without variation among animals and develop both pressure-overload-and volume-overloadinduced cardiac hypertrophy only when fed a high salt diet. 14 -16 DS rats show not only salt-sensitive hypertension but also hypertriglyceridemia and hyperinsulinemia, 21,22 suggesting that DS rats have some features similar to human hypertension. It has also been reported that expression levels of interleukin-1␤ and monocyte chemoattrac-tant protein-1 are increased in the left ventricle of DS rats.…”
Section: Discussionmentioning
confidence: 99%